Narratives of Judgement: Representations of “Privileged” Jews in Holocaust Documentaries - Adam Brown (Revue LISA)
Auschwitz survivor Primo Levi’s highly influential essay, “The Grey Zone”, explores the taboo issue of “privileged” Jews, those prisoners who were forced to cooperate with their Nazi captors in order to prolong their lives or the lives of their families. Levi argues that moral evaluations of privileged Jews should be suspended; however, judgements of these liminal figures have permeated representations of victims’ experiences. Taking Levi’s reflections on the “grey zone” as a point of departure, I analyse the ways in which a number of Holocaust documentary narratives construct problematic judgements of privileged Jews; nonetheless, it will be shown that some films engage with the issue in a nuanced manner. While Levi singles out the medium of film as particularly predisposed to simplistic judgements, I argue that documentary film has considerable potential to offer a complex representation of the extreme ethical dilemmas that privileged Jews faced.